The EFFECT OF CONSUMER SATISFACTION AND BRAND CHOICE ON CONSUMER LOYALTY MAHAR AGUNG ORGANIZER - Wijayanto, Dwi (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
Competition in the Event Organizer (EO) and Wedding Organizer (WO) businesses in Surabaya and its surroundings is increasing, so it is important to pay attention to consumers to stay loyal to the business. Mahar Agung Organizer, who is one of the EOs and WOs in Surabaya, found a problem phenomenon regarding the significant decline in the number of clients from 2018-2020. This indicates that consumer loyalty and brand choices from consumers towards EO services, especially at Mahar Agung Organizer, have also decreased. This study aims to examine and analyze consumer satisfaction and brand choice on consumer loyalty at Mahar Agung Organizer. This research approach is in the type of quantitative research with simple random sampling totaling 75 samples from the Mahar Agung Organizer customer population for the period 2018-2019, amounting to 300 customers. The method of data collection by distributing online questionnaires was measured using a Likert scale. The research data analysis technique used multiple linear regression analysis with the help of SPSS. The results of this study found that, Customer Satisfaction has a significant effect on Consumer Loyalty at Mahar Agung Organizer and Brand Choice has a significant effect on Consumer Loyalty at Mahar Agung Organizer.